Bis[?-4,5-dicyano-N,N?-bis(p-tolylsulfonyl)-o-phenylenediaminato]bis[diamminecopper(II)]dihydrate - Yüksel, Fatma; Tuncel, Sinem; Guerek, Ayse Guel; Jeanneau, Erwann; Luneau, Dominique; Ahsen, Vefa (Blackwell Publishing, 2007)
The title complex, [Cu-2(C22H16N4O4S2)(2)(NH3)(4)]center dot 2H(2)O, is a centrosymmetric dimer. The two copper ions are bridged by two 4,5-dicyano-N,N'- bis(p-tolylsulfonyl)-o-phenylenediamine ligands; the Cu center dot center dot center dot Cu distance is 8.749 (1) angstrom. Each copper ion is in a distorted square-pyramidal geometry, defined by two N atoms from one ligand, two N atoms from two coordinated ammonia molecules and one CN from the other ligand apically. The hydrogen-bonding network leads to a layered structure.
Keywords: Phthalocyanines